Stigma, discrimination, and attitude towards the Chinese community in the USA and Canada during the outbreak of COVID-19 - Sanyaolu, Adekunle; Okorie, Chuku; Marinkovic, Aleksandra; Abbasi, Abu; Mangat, Jasmine; Younis, Sadaf; Chan, Henry; Jaferi, Urooj (Social Determinants of Health, 2020)
Background: The COVID-19 outbreak, declared a global pandemic by the WHO, raises some serious health, as well as discrimination concerns worldwide. This study outlines the knowledge, stigma, and discrimination of people towards the Chinese community in the USA and Canada at the onset of the pandemic. Methods: An online community-based, opt-in descriptive survey was conducted spring of 2020. The study collected data with anonymity about demographics, travel history, COVID-19 knowledge, awareness, as well as stigmatization and discrimination against the Chinese community. Data was compiled with excel using descriptive statistics and Chi-square for the analysis. Results: Among 172participants, the highest number of responses came from the 21 to 40-year-old age groups. There was some reported stigma against the Chinese community in the study, particularly during the early days of the outbreak; 6.4% participants indicated that only Chinese infected COVID-19 individuals need to be quarantined with 13.4% avoiding only the Chinese community; Furthermore, 30% blamed people from China for the COVID-19 outbreak; while 13% people said they would avoid Chinese people and/or their communities. Results from the study suggest that those who live in urban settings, who are married and hold university degrees have a better understanding of the infection, knowledge of how it spreads, and also are less likely to discriminate against the Chinese community or blame the Chinese from China for COVID-19. Conclusion: Lack of knowledge caused anxiety and fear among some people, which thus played the main role in the rising cases of Chinese community stigma and discrimination reported.